Nanomaterials-based solid phase extraction and solid phase microextraction for heavy metals food toxicity. (November 2020) - Khan, Wajid Ali; Arain, Muhammad Balal; Soylak, Mustafa
Abstract: In the last few years, nanomaterials are widely used sorbents for the extraction of heavy metals in food samples. The nanomaterials have a larger surface area and show high selectivity, fast adsorption capability, and high efficiency for food contaminants (heavy metals). Carbon nanomaterials (CNMs), magnetic nanoparticles (MNPs), nano-imprinted polymers (NIPs), nano-based metal-organic frameworks (N-MOFs), and silica nanoparticles (SiNPs) are most prominent nanomaterials used in the preconcentration and determination of heavy metals. The most popular sorbent-based techniques for the extraction of heavy metals are solid phase extraction (SPE) and solid phase microextraction (SPME). The use of these nanomaterial sorbents increases the extraction efficiency of both techniques. This review summarizes the nanomaterial sorbents (published 2015 to May-2020) used in solid phase extraction (SPE) and solid phase microextraction (SPME) for heavy metals extraction in food. Graphical abstract: Image 1 Highlights: Nanomaterials are widely used sorbents for the extraction of heavy metals in food. The main advantage of nanomaterials is the larger surface area for heavy metals. The use of nanomaterial sorbents increases the extraction efficiency of SPE and SPME.